Explaining the transparency of local government websites through a political market framework - Tavares, António F. (2020)
This paper contributes to the literature on government transparency by addressing the question of what drives the differences in local government levels of transparency. Our main objective is to ascertain whether transparency is mainly driven by the leadership, capacity and other political traits of the local governments themselves – “supply-side determinants” – or, rather, if it hinges on social, cultural and/or other local community factors (“demand-side” determinants). We test the hypotheses derived from this theoretical framework using the results of the Municipal Transparency Index which is based on the information disclosed in the local governments' official websites and was applied to all Portuguese municipalities for the first time in 2013. Our findings indicate that municipalities with less financial autonomy, run by male mayors, with a larger number of consecutive terms in office, and smaller margins of victory in local elections display lower levels of transparency. On the demand-side, the unemployment rate and the average age of the municipal population emerge as the best predictors and are both negatively associated with transparency.